Exploring the effectiveness of pharmacy curriculum in Saudi Arabia in developing leadership skills among pharmacy students from their perspective: A mixed-methods study - Majid Ali; Aseel Alsreaya; Abdulrahman Alqarzi; Yazeed Alzahrani; Ibrahim Alhomood; Abdulaziz Alruhaimi; Abdulrahman Hijri; Ahmed Mobarki; Mohammed Najie; Mohammed Mashyakhi; Abdullwahab Bajawi (Elsevier, 2024)
Introduction: Leadership is an important component of pharmacy education. This study helps identify the strengths and limitations of the pharmacy curriculum in developing leadership skills among pharmacy students in Saudi Arabia and suggest how to improve the curriculum to better prepare them to become effective leaders in the healthcare profession. Methods: This study employed a mixed-methods research design with a sequential exploratory design. Phase I involved semi-structured interviews with student leaders of pharmacy student clubs/societies from different universities in Saudi Arabia. Interviews were recorded and transcribed verbatim. The written transcriptions were analyzed using thematic analysis. Phase II used a survey questionnaire to collect data from a larger sample of pharmacy students and interns from different universities in Saudi Arabia and the data is mainly presented as frequencies and percentages. Results: Eleven eligible participants were interviewed. Thematic analysis generated 288 codes which were categorized into 17 subthemes. These subthemes were further categorized into five overarching themes: Leadership development and acquisition; Skills and characteristics of effective leaders; Challenge and support for student leaders; Personal growth and benefits of leadership; Vision, goals and responsibilities of student leaders. The findings informed the development of the survey questionnaire which was completed by 484 students/interns. Mixed opinions were received regarding whether the pharmacy curriculum/program is helping or has helped the respondents develop leadership skills as well as whether the college has provided (or is providing) adequate support, resources or opportunities for the development of leadership skills. Eighty-eight per cent of the participants requested that the pharmacy curriculum in their college should include more courses or workshops focused on leadership development. They favoured several options from the listed topics to be included in these courses or workshops of which effective communication was the most prominent. Conclusion: This study highlights that pharmacy curriculum/colleges in Saudi Arabia promote essential leadership skills through various pedagogical approaches and support mechanisms to some extent. However, the students identified that the pharmacy curriculum needs to be revised in order to better prepare them for leadership positions.